Design of a Ceramic Brick Cutting Robot. (August 2020) - Peng, Sun
Abstract: Ceramic tiles are now widely used in indoor and outdoor decoration projects. Aiming at the shortcomings of the existing ceramic tile cutting machine, a ceramic tile cutting robot is designed. PLC is used as the control core of the robot to make the size adjustment of ceramic tile cutting convenient and flexible, the cutting error is small, the tile section is smooth and tidy, and the breakage rate is low, which improves the efficiency of ceramic tile cutting and reduces the labour intensity of workers.